MOST FREQUENT DISEASES IN CANINES IN VETERINARY CLINICS IN LIMA, PERU - Ceino -Gordillo, Franco (2020)
The dog is one of the oldest domestic animals in the world and man's best friend. Like us, dogs can suffer from various illnesses throughout their lives. Many of them can be cured and with a good prevention system, their eff ects can be avoided or minimized. Th is study determined which are the most common diseases and conditions in canines with the information collected from veterinary clinics in Lima, Peru, from 2013 to 2018. For this purpose, a total of 841 clinical records from diff erent Lima veterinarians were collected and cataloged related to these diseases. A total of 269 cases was enclosed in the study, resulting in 65 of dermatitis (7.72%), 40 males and 25 females; 59 of fracture (7.01%), 48 males and 11 females; 56 of gastroenteritis (6.65%), 41 males and 15 females; 52 of otitis (6.18%), 44 males and 8 females; and 37 of Demodex Owen, 1843 (4.39%), 27 males and 10 females. Besides, these diseases were classifi ed according to age ranges (0-14 months, 14 months-9 years, over 9 years) that results in a higher prevalence in young canines and young adults (14 months-9 years) being the breeds with the higher predominance of cases the mestizo or cross (108 cases/40%), Bulldog (15 cases/5.8%), Shih Tzu (15 cases/5.8%), beagle (13 cases/4.8%) and pitbull (12 cases/4.5%), respectively. With this study, information was collected about the most common diseases and conditions in canines in Lima, Peru.